Oral administration of edelfosine encapsulated lipid nanoparticles causes regression of lung metastases in pre-clinical models of osteosarcoma. (28th August 2018) - González-Fernández, Yolanda; Brown, Hannah K.; Patiño-García, Ana; Heymann, Dominique; Blanco-Prieto, María J.
Abstract: Osteosarcoma (OS) is the most frequent paediatric bone cancer, responsible for 9% of all cancer-related deaths in children. In this paper, a new strategy based on delivering edelfosine (ET) in lipid nanoparticles (LN) was explored in order to target the primary tumour and eliminate metastases. The in vitro and in vivo efficacy of the free drug, drug loaded into lipid nanoparticles (ET-LN) and doxorubicin (DOX) against osteosarcoma (OS) cells was analysed. ET and ET-LN decreased the growth of OS cells in vitro in a time- and dose-dependent manner. Interestingly, the uptake of ET and ET-LN was lower when OS cells were pre-treated with DOX. In vivo studies revealed that ET and ET-LN slowed down the primary tumour growth in two OS models. However, the combination of both drugs showed no additional anti-tumour effect. Importantly, ET-LN successfully prevented the metastatic spread of OS cells from the primary tumour to the lungs. On the whole, ET-LN are a promising candidate for OS chemotherapy. Highlights: Edelfosine and edelfosine loaded lipid nanoparticles inhibit osteosarcoma cell proliferation in vitro . The uptake of ET and ET-LN is decreased when osteosarcoma cells are pre-treated with doxorubicin. Orally administered ET-LN have an outstanding effect against primary OS tumours. ET-LN successfully prevented the metastatic spread of OS cells from the primary tumour to the lungs.